MicroRNA-223 coordinates cholesterol homeostasis - Vickers, Kasey C; Landstreet, Stuart R; Levin, Michael G; Shoucri, Bassem M; Toth, Cynthia L; Taylor, Robert C; Palmisano, Brian T; Tabet, Fatiha; Cui, Huanhuan L; Rye, Kerry-Anne; Sethupathy, Praveen; Remaley, Alan T (Proceedings of the National Academy of Sciences - PNAS, 2014)
MicroRNAs (miRNAs) regulate a wide variety of biological processes and contribute to metabolic homeostasis. Here, we demonstrate that microRNA-223 (miR-223), an miRNA previously associated with inflammation, also controls multiple mechanisms associated with cholesterol metabolism. miR-223 promoter activity and mature levels were found to be linked to cellular cholesterol states in hepatoma cells. Moreover, hypercholesterolemia was associated with increased hepatic miR-223 levels in athero-prone mice. miR-223 was found to regulate high-density lipoprotein-cholesterol (HDL-C) uptake, through direct targeting and repression of scavenger receptor BI, and to inhibit cholesterol biosynthesis through the direct repression of sterol enzymes 3-hydroxy-3-methylglutaryl-CoA synthase 1 and methylsterol monooxygenase 1 in humans. Additionally, miR-223 was found to indirectly promote ATP-binding cassette transporter A1 expression (mRNA and protein) through Sp3, thereby enhancing cellular cholesterol efflux. Finally, genetic ablation of miR-223 in mice resulted in increased HDL-C levels and particle size, as well as increased hepatic and plasma total cholesterol levels. In summary, we identified a critical role for miR-223 in systemic cholesterol regulation by coordinated posttranscriptional control of multiple genes in lipoprotein and cholesterol metabolism.